Comercio, conflictos y alianzas en la frontera luso-española: Capitanía de Río Negro y provincia de Maynas, 1780-1820 (Estudios) - Bastos, Carlos Augusto (2015)
In the colonial period, the Spanish politics towards the American frontiers was oriented not only to recognition and military protection of the borders, but also to control trade in the regions. During the demarcation of the boundaries in the 18th Century, the smuggling in the borders degenerated in various conflicts between the Spanish and Portuguese authorities. However, illegal trade played an important role en la satisfaction of the provisions in the zone, making possible the establishment of local alliances. This article addresses these questions taking as object the study the border Luso-Spanish in the Amazon Valley, between captaincy of Negro River and the province of Maynas, 1780-1820.